A CORRECTED COHESIVE ZONE MODEL IN THE INTERLAMINAR FRACTURE OF COMPOSITE - JIA YunLong; XU Lin; XIANG Bin (Jixie qiangdu)
In order to consider both material damage of the crack tip and the initial fracture toughness,a corrected cohesive zone model（ CZM） that considers the influence of material damage of the initial crack propagation has been proposed. The corrected cohesive zone mode obtained from the end notch flexure（ ENF） test has been implemented in the ABAQUS/Standard.The results show that it is necessary to consider both material damage of the crack tip and the initial fracture toughness,and the corrected cohesive zone mode can accurately simulate the crack propagation.